The Effect of Safety Leadership To The Incident Medication Error in IFRS X Bintaro Through Officer Compliance Implements Standard Operations Procedure - Rachmawati Dewi, Agusdini Banun Saptaningsih, Muhammad Natsir Nugroho (Jurnal Cinta Nusantara, 2023)
Medication error is an unintentional error prescribing, transcribing, dispensing, administration or monitoring under the control of a pharmacist. A safe madication system needs to be developed and maintained to ensure that patients receive good drug care. This influence that can reduce the incidence medication errors at the X Bintaro Hospital Pharmacy Installation. The sample in this study were 30 staff working at the Pharmacy Installation. The research instrument used a questionnaire and was measured using a Likert scale. Research results: found that there was no significant negative effect on the knowledge of officers on the incident medication errors (tcount<ttable (0.558<2.045) and significance (pvalue) 0.582>0.05) in the Pharmacy Installation of X Bintaro Hospital. Implications and Suggestions: The need for education not to be afraid to report (blame culture), the need to monitor and evaluate the achievement of pharmaceutical quality indicators, and the need to directly improve the service system to be more efficient and effective in order to be able to improve the quality of pharmaceutical services that focus on occupational and patient safety.